Non-chemical signalling between mitochondria - Mould, Rhys R.; Kalampouka, Ifigeneia; Thomas, E. Louise; Guy, Geoffrey W.; Nunn, Alistair V. W.; Bell, Jimmy D. (Frontiers in Physiology, 2023)
A wide variety of studies have reported some form of non-chemical or non-aqueous communication between physically isolated organisms, eliciting changes in cellular proliferation, morphology, and/or metabolism. The sources and mechanisms of such signalling pathways are still unknown, but have been postulated to involve vibration, volatile transmission, or light through the phenomenon of ultraweak photon emission. Here, we report non-chemical communication between isolated mitochondria from MCF7 (cancer) and MCF10A (non-cancer) cell lines. We found that mitochondria in one cuvette stressed by an electron transport chain inhibitor, antimycin, alters the respiration of mitochondria in an adjacent, but chemically and physically separate cuvette, significantly decreasing the rate of oxygen consumption compared to a control (p = <0.0001 in MCF7 and MCF10A mitochondria). Moreover, the changes in O2-consumption were dependent on the origin of mitochondria (cancer vs non-cancer) as well as the presence of "ambient" light. Our results support the existence of non-chemical signalling between isolated mitochondria. The experimental design suggests that the non-chemical communication is light-based, although further work is needed to fully elucidate its nature.